A supramolecular single-site photocatalyst based on multi-to-one Förster resonance energy transfer. Issue 34 (30th March 2021) - Ji, Yi; Zuo, Quan; Chen, Chuanshuang; Liu, Yannan; Mai, Yiyong; Zhou, Yongfeng
Abstract : A multi-to-one supramolecular photocatalyst with multiple graphene quantum dot antennas onto a single-Pt-site porphyrin catalytic center is fabricated for water splitting. Abstract : A multi-to-one supramolecular photocatalyst is fabricated by aqueous electrostatic self-assembly of multiple graphene quantum dot (GQD) antennas onto a single-Pt-site porphyrin unimolecular micelle (PtTHPD-UM ) catalytic center. Light energy is transferred from GQDs to PtTHPD-UM to catalyze water splitting into hydrogen up to 57 190 μmol g(Pt) −1 h −1 under visible light.